“It’s Much Easier to Love People by Reading Your Books”: The Correspondence of Maria Karamzina and Ivan Shmelyov (1934–1939) - Alexey M. Lyubomudrov (Литературный факт)
The article presents hitherto unpublished correspondence between the poet Maria Karamzina (1900–1942) and the writer Ivan Shmelyov (1873–1950), as two members of the Russian Diaspora. The letters are devoted to thoughts on the word art, modern literature, and their own work. Maria Karamzina emphasizes the spiritual and moral impact of Ivan Shmelyov’s books, notes the uniqueness of the prose writer figure, writing “about the most precious and important,” who is able to support his readers in a ghastly era. The correspondence is characterized by the maximum possible level of openness and almost a confessional tone. It shows both the character traits and mental states of the two writers, and reflects their family vicissitudes. The issues of the living of an Orthodox Christian occupy an important place in the dialogue of Maria Karamzina and Ivan Shmelyov. Descriptions of the literary, social, and ecclesiastical life of the Russian-speaking population in Estonia in the interwar period are of particular value. The introductory article analyzes the socio-political consciousness of a part of White Russian emigrants, who had hoped for a rightful place in Soviet Russia, but were deceived in their expectations. The article also provides a comparison of the topics, plots, and style of the epistolary communication of Maria Karamzina with Ivan Bunin and Ivan Shmelyov. Overall, this letter collection is of interest to experts in the field of the Russian Diaspora literature, as well as a wide range of readers. The appendix presents an unknown Maria Karamzina’s article “The Heavenly Ways” (1937).